(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
Mathematics is embedded in all areas of knowledge. In Fashion Design, mode- ling requires the modeler to have technical knowledge about measurements, fabrics, sewing technologies, as well as knowing how to interpret basic mathematics data, shapes, trends and calculations. Therefore, mathematical concepts constitute impor- tant aspects in the processes of flat and three-dimensional modeling. This article aims at analyzing, interdisciplinarily, from the student perspective, the relationship betwe- en mathematics and modeling, in the teaching-learning process of a higher education Fashion Design course. Then, an exploratory-comparative, qualitative-quantitative case study was carried out in the higher education course of Fashion Design, of a pri- vate college in Recife-PE. It was observed that students recognize their lack of basic mathematical knowledge and see interdisciplinarity as an alternative to solve this pro- blem. Apart from this, the low knowledge of Fashion Design students about mathe- matics interferes negatively in the adequate development of modeling knowledge.